2011
DOI: 10.1002/smll.201002000
|View full text |Cite
|
Sign up to set email alerts
|

LiFePO4 Mesocrystals for Lithium‐Ion Batteries

Abstract: Olivine LiFePO(4) is considered one of the most promising cathode materials for Li-ion batteries. A simple one-step, template-free, low-temperature solvothermal method is developed for the synthesis of urchinlike hierarchical mesocrystals of pristine LiFePO(4) as well as carbon-coated LiFePO(4) composites. Each urchinlike mesocrystal consists of LiFePO(4) sheets self-assembled via a dipolar field in spheres during a solvothermal process under the influence of Cl(-) anions. The obtained primary sheets of LiFePO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 55 publications
1
57
1
Order By: Relevance
“…LiFePO 4 has been extensively studied as a cathode material of Li-ion batteries since 1997 [1] owing to its environmental friendliness, lower cost and higher safety [2,3]. Many strategies can improve the electrochemical property of the LiFePO 4 , such as coating a conductive carbon [4,5] to enhance the ionic and electronic conductivity, doping with cations or anions to improve bulk property [6,7], and tailoring particle size and morphology to shorten the path of Li-ion migration [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LiFePO 4 has been extensively studied as a cathode material of Li-ion batteries since 1997 [1] owing to its environmental friendliness, lower cost and higher safety [2,3]. Many strategies can improve the electrochemical property of the LiFePO 4 , such as coating a conductive carbon [4,5] to enhance the ionic and electronic conductivity, doping with cations or anions to improve bulk property [6,7], and tailoring particle size and morphology to shorten the path of Li-ion migration [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…All diffraction peaks of P1(Fig. 3a)can be indexed to the Li3 PO 4 (JCPDS No. 25-1030), while the peaks of P2 (Fig.…”
mentioning
confidence: 99%
“…The authors reasoned that the disparity between the two materials may exist because of a pseudocapacitive effect in the mesocrystalline LFP imparted by its nanosized component. Similarly shaped LiFePO 4 mesocrystals formed through several other routes have been reported as well [138,139]. …”
Section: Cathodic Materialsmentioning
confidence: 97%
“…Su et al [98] reported a novel LiFePO 4 /graphene/carbon composite by an in situ solvothermal method to synthesize LiFePO 4 /graphene powders as precursors and then followed by a carboncoating process. The ethanol adopted in the experiment acted as a reducing agent, which was used to avoid the formation of undesirable ferric impurities in the solvothermal [99]. The results indicated that the co-modification of LiFePO 4 with graphene and carbon coating could construct an effective conducting network, which significantly enhanced the electrochemical activity of LiFePO 4 /carbon based composite.…”
Section: Preparation Of Compositesmentioning
confidence: 98%